Optimization of the Artemisia Polysaccharide Fermentation Process by Aspergillus niger - Tao, Ali; Feng, Xuehua; Sheng, Yajing; Song, Zurong (Frontiers in Nutrition, 2022)
In order to investigate the fermentation process of Artemisia polysaccharides, this paper showcases an investigation into the effects of fermentation time, fermentation temperature, strain inoculum, Artemisia annua addition, and shaker speed on the polysaccharides production of Artemisia annua. The yield of Artemisia polysaccharides content was determined based on the optimization of single-factor test, and then a response surface test was conducted with temperature, inoculum, and time as response variables and the yield of Artemisia polysaccharides as response values. The fermentation process was then optimized and the antioxidant activity of Artemisia polysaccharides was monitored using DPPH, ABTS+, OH, and total reducing power. The optimum fermentation process was determined by the test to be 5% inoculum of Aspergillus niger, temperature 36°C, time 2 d, shaker speed 180 r/min, and 4% addition of Artemisia annua, and the extraction of Artemisia polysaccharides was up to 17.04% by this condition of fermentation. The polysaccharides from Artemisia annua fermented by Aspergillus Niger had scavenging effects on DPPH, ABTS, and OH free radicals.